Dynamic simulation of tennis racket and string - Gu, Y. D.; Li, J.-S. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study is based on the finite element method, a computer simulation method, to analyse the dynamic property of tennis racket and string. A three-dimensional model was created in Solidwork according to the geometry of a mid-size graphite tennis racket. Recording the speed and position data of ball and string collision. Using Ansys to calculate the modal frequency and shape, the results illustrate that the fixed racket`s model frequency was smaller than free condition, and the string`s vibration character was meaningful to both devise and fix the damper.